The relationship between duration of subjective poverty and health among Chinese adults: Evidence from the China Family Panel Study - Cao, Dan; Zhou, Zhongliang; Ren, Yangling; Deng, Qiwei; Zhai, Xiaohui; Liu, Guanping; Zhao, Dantong; Zhao, Yaxin; Shen, Chi (Frontiers in Public Health, 2022)
Introduction The disadvantaged socioeconomic status could have accumulated negative effects on individual. In the Chinese context, studying subjective and relative poverty is more important under the implementation of the Targeted Poverty Alleviation campaign. This study aims to provide evidence of the relationship between the duration of subjective poverty and both physical and mental health among Chinese adults, using nationally longitudinal data from 2010 to 2018. Materials and methods Data were extracted from a nationally representative survey database—the China Family Panel Study (CFPS). The total sample size contains 12,003 adults, with 3,532 in the urban area and 8,471 in the rural area. Self-rated health and depressive symptoms were set as indicators of physical health and mental health, respectively. The duration of subjective poverty was measured by self-rated income level in the local area from 2010 to 2016. A series of ordinary least square regression was adopted to measure the relationship between duration of subjective poverty and health. Results For the urban residents, the average duration of subjective poverty is 1.99 time points, while 1.98 time points for the rural residents. Net of objective poverty, duration of subjective poverty has a significantly negative association with individual's self-rated health in the rural sample (Coef. = −0.10, p < 0.001). Compared with those who have not experienced subjective poverty, the self-rated health score of people who experienced four time points is likely to decrease by 0.54 in the rural area and 0.30 in the urban area. In terms of mental health, 1 unit increase in the duration of subjective poverty is related to 0.15 unit increase in Center for Epidemiologic Studies Depression Scale-8 (CES-D8) scores in the urban sample and 0.46 in the rural sample. Compared with those who have not experienced subjective poverty, the CES-D8 scores of people who experienced four time points are likely to increase by 1.47 in the rural area and 0.95 in the urban area. Conclusion A longer duration of subjective poverty has a cumulatively negative effect on Chinese residents' physical and mental health, especially in rural area. Our study advocates researchers and policymakers pay more attention to the cumulative effect of subjective poverty on health.